جودة الخدمة وأثرها على رضا الزبون في شركات النقل الجوي دراسة حالة شركة الطاسيلي للطيران وكالة تندوف - حيمد, محمد (جامعة الوادي - University of Eloued, 2022)
إن نجاح أي مؤسسة مرهون بأداء المورد البشري ومدى كفاءته، لأنه العنصر الاساسي في تقديم جودة المنتج او الخدمة فالمؤسسات الخدمية خاصة اصبحت مطالبة بتقديم خدمات تتوافق مع رغبات وتطلعات الزبائن حتى تضمن رضاهم وولائهم للمؤسسة. في هذه الدراسة قمنا بتسليط الضوء على أهمية جودة الخدمة في تحقيق رضا الزبائن على مستوى شركة الطيران طاسيلي وكالة تندوف وهذا بالاعتماد على ابعاد جودة الخدمة التي تتمثل في: الملموسية، الاعتمادية، الاستجابة، التعاطف وباقي الأبعاد الأخرى بحيث تم الاعتماد على الاستبيان وتوزيعه على عينة من زبائن الشركة والذين يستخدمون الحطوط الداخلية باتجاه ولاية تندوف، وتأكد النتائج المتوصل اليها على وجود علاقة ذات دلالة احصائية بين جودة الخدمة التي تقدمها شركة الطاسيلي للطيران و رضا الزبائن. The success of any enterprise depends on the performance of the Human Resource and its efficiency, and it is the main element in providing the quality of the product or service. The service companies have become required to provide services that satisfy the desires and aspirations of customers in order to ensure their satisfaction and loyalty to the institution.In this study, we shed light on the importance of service quality in achieving customer satisfaction at the level of Tassili Airlines Tindouf Agency, depending on the dimensions of service quality, which are: tangibility, reliability, response, sympathy and the rest of the other dimensions. We relied on the questionnaire and distributed it to a sample of customers of Company who use domestic airlines to wards the Wilaya of Tindouf, and the results obtained confirm the existence of a statistically significant relationship between the quality of service provided by Tassili Airlines and customer satisfaction
Service quality and its impact on customer satisfaction in air transport companies Case study of Tassili Airlines, Tindouf Agenc
مقال
Keywords: المورد البشري ،الخدمة، جودة الحدمة، شركة الطيران طاسيلي، رضا الزبون.; Human Resource, Service, Service Quality, Tassili Airlines, Customer Satisfaction.